Musical devices in neurological rehabilitation in the upper limb: an integrative review (Research, Society and Development, 2022)
Introduction: Neurologic rehabilitation of upper limb is a challenge process require patient high adherence to therapeutic protocol for effective results. One of the strategies to promote the neuroplasticity and the patient motivation is the use of music in rehabilitation. The progress in the field motivate the development of music devices/games that aim rehabilitation be ludic, functional and less tiring. Objetives: To synthesize and analyze through an integrative review the benefits, usability, limitations and possible improvements of devices for neurological recovery. Methods: Research articles use the data bases dados PubMed, Scielo, PeDro and Cochrane Library. Used the follow keywords: “Music Intervention”, “Rehabilitation”, “Music Device”, “Neurologic Disease”, “Upper Limb”, along with the booleans “and” and “or”, seek in tittle and abstract of the articles. Was admitted articles with no more that 10 years of publication and we did not exclude any language. Results: Was found 5 articles the satisfied the inclusion criteria. The devices were developed to attend patients with Stroke and Parkinson Disease. The main benefits were increased repetition of tasks, improvement in rhythmic skills, increased coherence cortico-muscular, increase of voluntary motivation and improvement smoothness of movements. Conclusion: The use of music devices in neurologic rehabilitation of upper limb proves beneficial, viable and without apparent risks. Although, there are a scarce number of articles, principally randomized clinical trials, beyond samples not so representative, it´s necessary more studies to validate the use of this devices.